Marine borers resistance of chemically modified portuguese wood - Barroso Lopes, Duarte; Mai, Carsten; Militz, Holger (Maderas. Ciencia y Tecnología, 2025)
This study deals with the role of hardness and chemical toxicity in the resistance of pinewood to marine borers. Portuguese wood Maritime pine (Pinus pinaster) was modified with 1,3-dimethylol 4,5-dihydroxy ethylene urea (DMDHEU), methylated methylol melamine (MMF), tetraethoxysilane (TEOS) and two types of wax. In addition, for comparative purposes, different control species, Ipê, Beech and Blue Gum and CCA treated pine were included. All specimens were exposed over 2 years in sea (Porto, north of Portugal). Three inspections were performed after exposure (6, 12 and 24 months). The influence of type and level of modification as well as hardness was evaluated. As results: Specimens modified with resin have shown slight or trace attack by Teredinids in DMDHEU with low level of modification (10% of weight percent gain, WPG); MMF resin with high and low level of modification (25% and 10% of WPG) have shown trace to moderate attack, respectively. With the TEOS and wax impregnated wood which fill the cell lumens no significant difference in marine borers attack was found as compared to unmodified control specimens, despite the increased hardness.